Cell cycle regulator MYBL2 is a distinct vulnerability in acute myeloid leukemia - Küchler, Sandra; Brilloff, Silke; Schäfer, Silvia Maria; Rahimian, Elahe; Kufrin, Vida; Peri, Shraddha S.; Musa, Julian; Grünewald, Thomas G. P.; Schewe, Denis M.; Ball, Claudia R.; Bornhäuser, Martin; Glimm, Hanno; et al. (Cell death discovery, 2025)
Acute myeloid leukemia (AML) is a hematologic malignancy characterized by the accumulation of myeloid blasts in the bone marrow. Despite the availability of potential curative treatments, patients frequently experience unfavorable outcomes. One crucial aspect contributing to relapse is the plasticity of leukemic clones, which enables them to switch between active proliferation and dormancy. The adaptability of AML underscores the need for novel therapies targeting AML-specific proteins. To address this, genome-wide CRISPR screens can be utilized to identify cancer entity-specific vulnerabilities. Leveraging publicly available functional genomics datasets and comparing AML with non-AML cancer cell lines, we identified a significant dependency on the cell cycle-regulating gene MYBL2 in AML. We describe MYBL2 as a key driver of AML cell growth and proliferation, highlighting its established role as a cell cycle regulator. Also, our findings uncover its previously unrecognized function as an inhibitor of cellular senescence. A knockdown of MYBL2 induces cell cycle arrest in the G2/M phase with subsequent induction of apoptosis in vitro, and reduces leukemic burden in a patient-derived xenograft (PDX) model in vivo. Interestingly, some AML cells evade apoptosis and enter a senescent-like phenotype upon MYBL2-knockdown, which is reversible upon re-expression of MYBL2. Finally, analyses of clinical data from two publicly available patient cohorts demonstrate a lower probability of survival in patients with higher MYBL2 expression, further hinting at the potential relevance of MYBL2 in AML. In conclusion, our findings demonstrate the essential role of MYBL2 in AML, governing the balance between cell proliferation, cell survival and senescence, ultimately influencing the fate of AML cells.
Gesehen am 13.02.2026